Perkembangan Kesenian Bangreng di Kabupaten Sumedang Tahun 1969-2020 - Ainun Nur Intan Fadilah (UIN Sunan Gunung Djati Bandung, 2025)
This article asserts the significance of Bangreng Art, which was established in 1969 by Abah Maman Suharya. Bangreng Art is a direct evolution of Terbang and Gembyung art, with Terbang art playing a crucial role in spreading Islam throughout the Sumedang Regency. While anchored in Islamic teachings like prayer and dhikr, the rituals are still executed in accordance with Hindu cultural norms. Research unequivocally shows that Bangreng Art stands as a unique artistic expression in Sumedang Regency, deeply rooted in Terbang art and its mission to promote Islamic teachings. Initially, Bangreng Art enjoyed immense popularity within the Sumedang community. However, by the 2000s, it reached a critical saturation point. In response, the Sumedang Regency government has taken decisive action to preserve Bangreng Art through three key strategies: robust protection, strategic development, and meaningful utilization.